Titik Kritis Penentuan Awal Puasa dan Hari Raya di Indonesia - Maskufa & Wahyu Widiana (Universitas Islam Negeri Jakarta, 2012)
Abstract: The Critical Points of Determining the Fasting Month and Feast Day in Indonesia. There are four major madzhab in determination the fasting month and feast day in Indonesia, namely: madzhab of ru’yah al-hilâl, madzhab of hisâb wujûd al-hilâl, madzhab of imkân al-ru‘yah, and madzhab of global ru‘yah. The four madzhabs have different criteria in ascertaining the commencement of the fasting month and the celebration after fast (lebaran). When the position of the moon does not fulfill the criteria, then it is almost ascertainable by the differences that appear. However, if the position of the moon is under the horizon or passes a minimum limit, then the difference will not happen.Keywords: ru’yah al-hilâl, hisâb wujûd al-hilâl, imkân al-ru’yah, global ru’yah.Abstrak: Titik Kritis Penentuan Awal Puasa dan Hari Raya di Indonesia. Ada empat mazhab besar dalam penentuan puasa dan hari raya di Indonesia, yakni: mazhab rukyah hilal, mazhab hisab wujûd al-hilâl, mazhab imkân al-ru’yah, dan mazhab rukyah global. Keempat mazhab tersebut mempunyai kriteria yang berbeda-beda dalam memastikan saat mulai puasa dan berlebaran. Ketika keadaan hilal tidak memenuhi kriteria yang ada, maka hampir dapat dipastikan perbedaan akan muncul. Akan tetapi, bila keadaan hilal sudah di bawah ufuk atau melampaui batas minimal imkân al-ru’yah, maka perbedaan tidak akan terjadi.Kata Kunci: ru’yah al-hilâl, hisâb wujûd al-hilâl, imkân al-ru’yah, rukyah globalDOI: 10.15408/ajis.v12i1.981